GATA‐binding protein 3 and gross cystic disease fluid protein 15 as a potential diagnostic marker for extramammary Paget's disease. Issue 6 (13th July 2021) - Kado, Soichiro; Kamiya, Koji; Jin, Meijuan; Kimura, Miho; Hossain, Md Razib; Maekawa, Takeo; Komine, Mayumi; Ohtsuki, Mamitaro
Abstract: Objectives: The aim of this study was to evaluate the expression of GCDFP15 and GATA‐binding protein 3 (GATA‐3) in extramammary Paget's disease (EMPD) skin and serum samples and to assess their availability as tumor markers for the diagnosis and assessment of disease severity in primary EMPD. Methods: Skin samples and serum samples were obtained from 16 patients with primary EMPD (10 cases from male, six cases from female; stage IA six cases, stage IB seven cases, stage III one case, stage IV two cases). By immunohistochemistry, the expression of GCDFP15 and GATA3 was examined in skin specimens. The serum levels of GCDFP15 and GATA3 were quantified by ELISA. Results: In our study, eight out of 16 patients showed positive staining for GCDFP15. In contrast, all 16 patients showed positive staining for GATA‐3. Immunohistochemical staining of EMPD skin samples showed that GATA‐3 had a higher positivity rate than GCDFP15. However, there was no correlation between serum levels of GCDFP15 or GATA‐3 and the disease stage. Conclusion: Our results indicate that GCDFP15 and GATA‐3 are useful for the diagnosis of primary EMPD, but not for monitoring disease progression, and suggest that GATA‐3 is a more reliable marker than GCDFP15 for the diagnosis of primary EMPD. Abstract : GATA‐binding protein 3 (GATA‐3), which has been identified as a highly sensitive nuclear marker for breast carcinoma and is more sensitive than gross cystic disease fluid protein 15 (GCDFP15) in this context, is highly expressed in apocrine glands and adnexal tumors. Given the origin of extramammary Paget's disease (EMPD) and the similarity between EMPD and breast carcinoma, we hypothesized that GATA‐3 could be a sensitive diagnostic marker for EMPD. In this study, we analyzed the expression of GCDFP15 and GATA‐3 in skin and serum samples and assessed their availability as tumor markers in primary EMPD. Our results suggest that GATA‐3 is a more reliable marker than GCDFP15 for the diagnosis of primary EMPD.